ANALISA PERBANDINGAN BREADTH-FIRST SEARCH DAN DEPTHFIRST SEARCH PADA APLIKASI SISTEM PAKAR PENGOBATAN TRADISIONAL - Irisma Ifrisma; Anton Setiawan Honggowibowo; Nurcahyani Dewi Retnowati (Institut Teknologi Dirgantara Adisutjipto, 2013)
This research was conducted based on the need for tools for parents who have had children in determining a traditional medicine to treat illnesses suffered by children, toddlers and babies. Aids in the fo rm o f an expert system of traditional medicine. This expert system application can be run in a way that the disease name input experienced by children, toddlersand babies, then the expert system will provide information prescription medications to treat the disease. Search method used is the method of Breadth-First Search and Depth-First Search. Results of comparative analysis o f Breadth-First Search and Depth-First Search was concluded that the analysis using the Depth-First Search more quickly provide information about traditional medicine in comparison with using the method of Breadth-First Search. However, the use of the method of Breadth-First Search is superior compared with Depth-FirstSearch. This is because the method of Breadth-First Search will not find a dead end or to find a solution although it has only one solution. And if you have two solutions, the method of Breadth-First Search will find them. The test results of the application of expert system of traditional medicine in the 30 responders was 72.67%. Thus, the application of expert systemof traditional medicine by using Breadth-First Search and Depth-First S earch good.